1976
DOI: 10.1530/jrf.0.0480061
|View full text |Cite
|
Sign up to set email alerts
|

Production, chemical composition and prostaglandin F-2  content of uterine fluid in pregnant sheep

Abstract: Summary. A uterine pouch was prepared surgically in ewes before mating to study the production and chemical composition of uterine secretions during pregnancy. Pregnancy was established in 6 sheep and in the first 55 days uterine fluid was present in small amounts (<5 ml), whereas between 109 days post coitum and 3 days post partum the volume ranged from 90 to 775 ml.The chemical composition of uterine fluid in pregnancy differed from that of plasma especially in respect of its high concentration of total calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…However, Ca 2+ concentration was modulated during different stages of the estrous cycle in bovines, with highest activity in early‐luteal and follicular stage ULFs (Schultz et al, 1971). Similarly, a four‐ to fivefold increased Ca 2+ concentration was found in 115‐day pregnant sheep ULF as compared to that of non‐pregnant (Harrison et al, 1976). It is possible that Ca 2+ level of buffalo ULF is modulated during the estrous cycle and involved in regulating the activity of these gelatinases/MMPs.…”
Section: Discussionmentioning
confidence: 85%
“…However, Ca 2+ concentration was modulated during different stages of the estrous cycle in bovines, with highest activity in early‐luteal and follicular stage ULFs (Schultz et al, 1971). Similarly, a four‐ to fivefold increased Ca 2+ concentration was found in 115‐day pregnant sheep ULF as compared to that of non‐pregnant (Harrison et al, 1976). It is possible that Ca 2+ level of buffalo ULF is modulated during the estrous cycle and involved in regulating the activity of these gelatinases/MMPs.…”
Section: Discussionmentioning
confidence: 85%
“…PLA-2 is then activated by the Ca2 + to release arachidonic acid, which is then metabolized predominantly into PGF-2a. Support for this proposal is provided by the previous finding that uterine fluid in sheep contains high concentrations of PGF-2a, calcium and protein (Harrison, Heap & Poyser, 1976). In early pregnancy, the conceptuses must prevent this proposed process in some way.…”
Section: Discussionmentioning
confidence: 88%
“…The fact that the response is blocked argues for a direct action of progesterone on the myometrium, although this might not be so if transfer of PGs from the lumen to the myometrium was impaired by progesterone. This possibility would seem remote because synthesis of PGs by the endometrium is enhanced by progesterone (Louis, Parry, Robinson, Thorburn & Challis, 1977) and Harrison, Heap & Poyser (1976) have shown that both uterine fluid and uterine vein blood contain substantial amounts of PGs (i.e. synthesis and re¬ lease are unimpaired) in ewes with high plasma progesterone levels.…”
Section: Discussionmentioning
confidence: 99%